A highly differentiated glomeromycotean association with the mucilage-secreting, primitive antipodean liverwort Treubia (Treubiaceae): clues to the origins of mycorrhizas - Duckett, Jeffrey G.; Carafa, Anna; Ligrone, Roberto (2006)
Thallus anatomy in three species of the primitive liverwort genus Treubia (Metzgeriidae, Treubiales) was studied by light and electron microscopy. The thallus exudes copious mucilage, a feature shared elsewhere in liverworts only with the mycotrophic subterranean axes of the allied genus Haplomitrium. The central strand in the thallus midrib has a unique histological organization and harbors an intra- and intercellular infection by a glomeromycotean fungus that is far more highly differentiated than most of the glomeromycotean associations described to date. The fungus enters the thallus via clefts in the ventral epidermis along the midrib and colonizes the parenchyma above, forming intracellular coils and prominent, relatively short-lived, hyphal swellings. Above the zone with intracellular colonization is a tissue area containing mucilage-filled intercellular spaces; here the fungus is entirely intercellular and forms abundant pseudoparenchymatous structures and, in more mature parts of the thalli, large hyphae with thick multistratose walls. Mucilage in Treubia differs in histochemistry and origin from that produced by apical papillae, via hypertrophied Golgi, in all other bryophytes. Remarkable parallels between fungal associations in Treubia, Haplomitrium, and Lycopodium, all members of very ancient lineages, suggest that these associations epitomize very early stages in the evolution of glomeromycotean symbioses.
Fot. byn., fot. col.
Keywords: Musgos; Micorrizas; Anatomia de la Planta